N2H4 as traceless mediator for homo- and cross- aryl coupling. Issue 1 (December 2018) - Lv, Leiyang; Qiu, Zihang; Li, Jianbin; Liu, Mingxin; Li, Chao-Jun
Abstract Transition-metal catalyzed couplings of aryl halides or arenes with aryl organometallics, as well as direct reductive coupling of two aryl halides, are the predominant methods to synthesize biaryls. However, stoichiometric amounts of metals are inevitably utilized in these reactions, either in the pre-generation of organometallic reagents or acting as reductant in situ, thus producing quantitative metal waste. Herein, we demonstrate that this longstanding challenge can be overcome with N2 H4 as a metal surrogate. The fundamental innovation of this strategy is that N2 and H2 are generated as side products, which readily escape from the system after the reaction. The success of both homo- and cross-coupling of various aryl electrophiles bearing a wide range of functional groups manifests the powerfulness and versatility of this strategy. Furthermore, both homo- and cross-couplings of a series of alkaloids, amino acids and steroids exemplify application of this protocol in the functionalization of biologically active molecules. Synthesis of biaryls by coupling strategies is unavoidably accompanied by stoichiometric metal waste. Here, the authors report the homo- and cross-electrophile coupling by using hydrazine as metal surrogate, only liberating N2 and H2 as side products.